Syzygium aromaticum Reduces Diabetes-induced Glucotoxicity via the NRF2/Glo1 Pathway - Do, Moon Ho; Choi, Jiwon; Kim, Yoonsook; Ha, Sang Keun; Yoo, Guijae; Hur, Jinyoung (Planta Medica, 2020)
Advanced glycation end products and methylglyoxal are known to show increased levels in diabetic conditions and induce diverse metabolic disorders. However, the antiglycation ability of the bark of Syzygium aromaticum is not yet studied. In this study, we determined the inhibitory effects of S. aromaticum on AGE formation. Moreover, S. aromaticum showed breakage and inhibitory ability against the formation of AGE-collagen crosslinks. In SV40 MES13 cells, treatment with the S. aromaticum extract significantly ameliorated MG-induced oxidative stress as well as cytotoxicity. Furthermore, in the S. aromaticum extract-treated group, there was a reduction in levels of several diabetic markers, such as blood glucose, kidney weight, and urinary albumin to creatinine ratio in streptozotocin-induced diabetic rats. Treatment with the S. aromaticum extract significantly increased the expression of nuclear factor erythroid 2-related factor 2, a transcription factor involved in the expression of antioxidant enzymes. Moreover, the treatment significantly upregulated the expression of glyoxalase 1 and downregulated the expression of receptor for AGEs. These results suggest that the S. aromaticum extract might ameliorate diabetes-induced renal damage by inhibiting the AGE-induced glucotoxicity and oxidative stress through the Nrf2/Glo1 pathway.
Keywords: Syzygium aromaticum; Myrtaceae; diabetes; AGEs; Nrf2